2017
DOI: 10.1016/j.redox.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of type I interferon responses by mitochondria-derived reactive oxygen species in plasmacytoid dendritic cells

Abstract: Mitochondrial reactive oxygen species (mtROS) generated continuously under physiological conditions have recently emerged as critical players in the regulation of immune signaling pathways. In this study we have investigated the regulation of antiviral signaling by increased mtROS production in plasmacytoid dendritic cells (pDCs), which, as major producers of type I interferons (IFN), are the key coordinators of antiviral immunity. The early phase of type I IFN production in pDCs is mediated by endosomal Toll-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 50 publications
2
40
0
1
Order By: Relevance
“…These results suggest that the dynamic regulation of ROS production, likely through the modulation of complex III, may act as a rheostat that regulates the magnitude of antiviral immune responses. Consistent with these findings, Agod et al found that mitochondrial superoxide drives increased MAVS protein expression in plasmacytoid DCs, increasing Akt and IRF3 activation and subsequent type I IFN production 57 . Wang et al showed shRNA knockout of SOD2 in cell lines increased viral replication and reduced antiviral responses 58 , likely a result of decreased mitochondrial H2O2 production, a known redox-sensitive activator of NF-κB and IRF signalling 47,59-61 .…”
mentioning
confidence: 80%
“…These results suggest that the dynamic regulation of ROS production, likely through the modulation of complex III, may act as a rheostat that regulates the magnitude of antiviral immune responses. Consistent with these findings, Agod et al found that mitochondrial superoxide drives increased MAVS protein expression in plasmacytoid DCs, increasing Akt and IRF3 activation and subsequent type I IFN production 57 . Wang et al showed shRNA knockout of SOD2 in cell lines increased viral replication and reduced antiviral responses 58 , likely a result of decreased mitochondrial H2O2 production, a known redox-sensitive activator of NF-κB and IRF signalling 47,59-61 .…”
mentioning
confidence: 80%
“…Various studies have demonstrated that ROS play a significant role in the inflammatory response. 36,37 ROS overproduction after LPS treatment induces secretion of cytokines, including TNF-, IL-1 , and IL-6, through the MAPK and NF-B pathways in HGFs. 8 P53 also increased the levels of these three cytokines in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Given that mtROS are highly compartmentalized and usually have biological actions within close vicinity of their production, we postulate that a negative regulatory effect of mtROS per se on cysteine 98 on TLR7 within the endosomal compartments is unlikely, due to the diffusion limited nature of ROS. However, a possible molecular mechanism for elevated type I IFN is the one proposed by Agod et al, through which mtROS suppress the phosphorylation of IRF7 in the cytosol, which is an important transcription factor for type I IFN expression by TLR7 and TLR9 signaling (1). Therefore, we envisage a complex regulation of type I IFN expression by subcellular-specific ROS, that is, endosome NOX2-derived ROS on C98 of TLR7 directly and mtROS targeting a critical downstream regulator of TLR7 function in IRF7.…”
Section: Discussionmentioning
confidence: 99%